UR_GERICHTE 98/99 15 vom 4. Dezember 1997 - UR Obergericht (1997)
Strassenverkehrsrecht. Art. 55, Art. 91 Abs. 1 SVG. Art. 2 Abs. 2 VRV. Art. 138 VZV. | Strassenverkehrsrecht. Art. 55, Art. 91 Abs. 1 SVG. Art. 2 Abs. 2 VRV. Art. 138 VZV. Fahren in angetrunkenem Zustand. Atemlufttest als Beweismittel.